若a=-5,a+b+c=-5.2,求代数式a²(-b-c)-3.2a(c+b)的值.求过若a=-5,a+b+c=-5.2,求代数式a²(-b-c)-3.2a(c+b)的值.

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/29 08:34:55
若a=-5,a+b+c=-5.2,求代数式a²(-b-c)-3.2a(c+b)的值.求过若a=-5,a+b+c=-5.2,求代数式a²(-b-c)-3.2a(c+b)的值.
x͑J@_T\LFn=d.IMl*+W.t+um1E ar|/·ʮ2?oWϋ"[|fIKEF4麸ȁi,?n62ʓI`:¼x4lce~;>:F[Dh:Mw (&"֧@%#xZ$,}sY<As&9%3CG8\!+0e+Ƙ mD9vC05(Z,}dq~Xd¾"Di$RHq:]Ŭ fz/Q]J5רv[k Rߥl]|b Sj2ܼY,۴h3ڷ0p}t

若a=-5,a+b+c=-5.2,求代数式a²(-b-c)-3.2a(c+b)的值.求过若a=-5,a+b+c=-5.2,求代数式a²(-b-c)-3.2a(c+b)的值.
若a=-5,a+b+c=-5.2,求代数式a²(-b-c)-3.2a(c+b)的值.求过
若a=-5,a+b+c=-5.2,求代数式a²(-b-c)-3.2a(c+b)的值.

若a=-5,a+b+c=-5.2,求代数式a²(-b-c)-3.2a(c+b)的值.求过若a=-5,a+b+c=-5.2,求代数式a²(-b-c)-3.2a(c+b)的值.

a=-5,a十b十c=-5.2,
则b十c=0.2
a²(-b-c)-3.2a(c十b)
=25(-0.2)-3.2(-5)(0.2)
=-5十3.2
=-1.8